Climate Smart Agriculture (CSA) monitoring framework to track adoption, outcomes, synergies and tradeoffs at household and farm level - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The CSV Monitoring framework was rolled out accross 8 Climate-Smart Villages in LAM, EA and SA and set up for SEA. Ca. 50 regional and local staff were trained and led its implemetnation covering 29 CSA options, 1,391 households and 2,337 farmers (51% women).